موارد ابن الصلاح في كتابه معرفة أنواع علوم الحديث: The Sources That Ibn Al-Salah Relied Upon in his Book "Maʿrifat Anwāʿ ʿUlūm Al-ḥadīth." - Yasser Muhammad Nuri Al-Dirshawi (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2022)
ملخص هذا البحث عبارة عن دراسة استقرائية إحصائية للموارد التي اعتمد عليها ابن الصلاح -رحمه الله تعالى- في كتابه "معرفة أنواع علوم الحديث"، حيث قام الباحث باستقراء الكتاب وحصر موارده وتقسيمها إلى موارد كتابية وغير كتابية، وما كان مفقوداً أو مخطوطاً من الموارد أشار إلى ذلك في الهامش، وقام بتوثيق المعلومة مرة واحدة من كتاب معرفة أنواع علوم الحديث ومن المورد الذي نقل المعلومة منه ولم يذكر اسمه، وبيّن شيوخه الذين لقيهم وسمع منهم، وبيّن من نقل عنهم بالوجادة، وكذلك من نقل عنهم دون أن يذكر المصدر، وترجم لهم الباحث بشكل موجز. وقد طرح الباحث مشكلتين في بحثه وهما: لماذا لقي كتاب معرفة أنواع علوم الحديث لابن الصلاح رحمه الله تعالى عناية العلماء بصورة لافتة؟ وما القيمة العلمية للموارد التي اعتمد عليها ابن الصلاح في كتابة معرفة أنواع علوم الحديث؟ وفيما يخص الأهداف، فإن هذا بحث يهدف إلى: حصر الموارد والمصادر التي اعتمد عليها ابن الصلاح في كتابه علوم الحديث، وبيان قيمة هذه المصادر وعلاقتها بهذا الفن، وقد توصل الباحث إلى أن الموارد التي اعتمد عليها ابن الصلاح - رحمه الله - قوية وأصيلة، ومتنوعة، وتميّز بدقة عزوه للمعلومات إلى مصادرها التي بلغت الكتابية منها مئة وثمانية وعشرين كتاباً، والسماعية ثمانية شيوخ، وبالوجادة عشرة شيوخ، وبلغت المصادر التي لم يذكرها خمسة عشر شيخاً، وقد أشار بقوله "رُوِّيْنا" إلى سماعه لتلك المعلومات من شيوخه، وليس من ذلك العالم مباشرة، وقد أورد بعض الكتب التي في غاية الأهمية ولكنها مفقودة أو مخطوطة. Abstract This research is an inductive statistical study of the sources that Ibn al-Salah relied upon in his book "Maʿrifat Anwāʿ ʿUlūm al-Ḥadīth." It contains an extrapolation of the book, limiting the sources and dividing them into written and non-written sources. However, the missing sources and the sources in the form of a manuscript are indicated in the footnote of the study. Additionally, the study referenced the information once from the book “Maʿrifat Anwāʿ ʿUlūm al-Ḥadīth", and from the source which the information was taken from. It also indicated the name of Sheikhs whom he met and heard from, and those who he has quoted from, as well as those who he quoted from them without mentioning the source. The study provided a brief biography of all of them. The researcher raised two problems: Why did Ibn al-Salah’s book "Maʿrifat Anwāʿ ʿUlūm al-Ḥadīth" received massive attention from scholars? What is the scientific value of the sources that Ibn al-Salah relied upon in writing the knowledge of the types of hadith sciences? Regarding the objectives, this research aims to: inventory the sources that Ibn Al-Salah relied upon in his book "ʿUlūm al-Ḥadīth.", and to show the value of these sources and their relationship in this science. The researcher concluded that the sources on which Ibn al-Salah relied upon, are strong, authentic, and varied. He was distinguished by the accuracy of his attribution of information to its sources, of which the written books amounted to one hundred and twenty-eight books, and the heard are eight Sheikhs. However, the sources that he did not mention were fifteen. Also, by his saying “Roweyna” he referred to what he heard from his Sheikhs, not directly from that scholar, and he mentioned some books that are important, but they are missing or in the form of manuscript.